Analisis Pengaruh Customer Perceived Value terhadap Kepuasan Pasien Umum pada Instalasi Rawat Inap Rumah Sakit Umum Daerah Kota Makassar - Mene Paradilla; Nurfitriani, Nurfitriani; Nurul Hidayah Nur; Andi Niartiningsih (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Customer satisfaction is a determinant of long-term success and survival in the health care industry and has attracted the attention of service providers in today's competitive conditions. Patient satisfaction refers to the extent to which a patient's expectations, goals, and preferences are met by a healthcare provider. This research aims to analyze the influence of customer perceived value on general patient satisfaction at the Inpatient Installation of the Makassar City Regional General Hospital. The type of research carried out was quantitative research using an observational study with a cross sectional study design, with a sample of 400 inpatients at the Makassar City Regional General Hospital. The results of the research show that patient satisfaction at the Makassar City Regional General Hospital is 47.5% with the most influential dimension on patient satisfaction from the customer perceived value variable, namely emotional value with a sig value of 0.001. The conclusion is that customer perceived value is 0.001<0.05 with a value of 43.6% which has a significant effect on patient satisfaction at the Makassar City Regional General Hospital.